(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study investigates in to the factors influencing job satisfaction of women police personnel in Thoothukudi District. Data was collected from 175 women police personnel using referral sampling technique. Findings of the present study will be useful for the police organisation, government and policy makers in formulating policies and procedures for the growth and development of women police personnel.